3-(Phenylimino)indolin-2-one - Al Subari, A.S.; Bouhfid, R.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The imino C=N double bond in the title compound, C(14)H(10)N(2)O, exists in an E conformation, with the phenyl ring being twisted by 80.7 (1)degrees in one independent molecule and by 81.4 (1)degrees in the other with respect to the plane of the indoline fused-ring system. The two independent molecules are linked by N-H center dot center dot center dot O hydrogen bonds, forming a zigzag chain running along the a axis.